Examining the Measurement Precision and Invariance of the Revised Get Ready to Read! - Farrington, Amber L. (J Learn Disabil, 2013)
Children's emergent literacy skills are highly predictive of later reading abilities. To determine which children have weaker emergent literacy skills and are in need of intervention, it is necessary to assess emergent literacy skills accurately and reliably. In this study, 1,351 children were administered the Revised Get Ready to Read! (GRTR-R), and an item response theory analysis was used to evaluate the item-level reliability of the measure. Differential item functioning (DIF) analyses were conducted to examine whether items function similarly between subpopulations of children. The GRTR-R had acceptable reliability for children whose ability level was just below the mean. DIF for a small number of items was present for only two comparisons—children who were older versus younger and children who were White versus African American. These results demonstrate that the GRTR-R has acceptable reliability and limited DIF, enabling the screener to identify those at risk for developing reading problems.